Intussusception in adults due to metastasis from renal cell carcinoma (Revista Argentina de Cirugía, 2026)
Intussusception, or intestinal invagination, is a rare cause of bowel obstruction in adults. An underlying organic cause is identified in most cases, with malignant tumors being the most prevalent etiology. For this reason, surgery is the treatment of choice in this age group. We present two clinical cases of adult patients diagnosed with intussusception secondary to metastases from renal cell carcinoma.  Both patients underwent enterectomy of the affected segment with end-to-end anastomosis. Thepathological examination revealed metastases of renal cell carcinoma. Both cases highlight the importance of a timely and accurate diagnosis of intussusception in adults, as well as the need for surgical treatment.
Keywords: intussusception; bowel obstruction; adult; metastasis; renal cell carcinoma